TOPICAL QUESTIONS OF OFFICERS’ PREPARATION AT CIVILIAN HIGHER EDUCATION INSTITUTIONS - Leonid Y. Rotkov; Alexandr N. Abramov; Anatoly V. Rug; Alexey V. Simonov (Высшее образование в России)
This work includes generalizing of the experiment results of the professional officers’ preparation (by the example of Nizhni Novgorod State University). It also gives an analysis of the realization versions of the military training program in conditions of two-tier education system including preparation direction of higher professional education “International region studies” on the “Bachelor” level. There is also given an analysis of special purpose citizens’ intake in higher education institutions for professional officers’ preparation programs in 2013 and suggestions for intake improvement.